2019
DOI: 10.1021/acs.energyfuels.9b00257
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Combustion Gases’ Radiation on Surface Temperature Measurements Using Two-Color Pyrometry

Abstract: This article developed an analytical two-color thermometry model combined with a mathematical radiative heat transfer model. The proposed model was used to investigate the performance of two-color pyrometry affected by absorption bands in hot combustion gases. This model was validated by comparing with a range of measured data and the results of other numerical solutions. The analysis of the temperature errors produced by a high-temperature H2O–CO2–N2 mixture in three measurement situations was presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In addition, it has been reported that using fiber optic spectrometers to study the polarization spectrum of an oil slick on the sea and monitoring the pollution of an oil slick on the sea surface through polarization spectrum [18,19]. The fiber optic spectrometers, as radiation signal measurement equipment, also have a wide range of applications in measuring emissivity and temperature on object surfaces [7][8][9][10][20][21][22][23][24]. Qiang Lu et al reported the temperature and emissivity of flame during biomass combustion, which is studied by utilizing a fiber optic spectrometer [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that using fiber optic spectrometers to study the polarization spectrum of an oil slick on the sea and monitoring the pollution of an oil slick on the sea surface through polarization spectrum [18,19]. The fiber optic spectrometers, as radiation signal measurement equipment, also have a wide range of applications in measuring emissivity and temperature on object surfaces [7][8][9][10][20][21][22][23][24]. Qiang Lu et al reported the temperature and emissivity of flame during biomass combustion, which is studied by utilizing a fiber optic spectrometer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on color images captured with color cameras, temperature distributions can be determined according to the radiation intensity captured by the optical channels. For calculation, the two-color method, which eliminates the influence of all other factors except the temperature, is widely used [24][25][26][27]. Huang et al [28] used an RGB pyrometer to measure the surface temperature of a deposit.…”
Section: Introductionmentioning
confidence: 99%